2010
DOI: 10.1055/s-0039-1699436
|View full text |Cite
|
Sign up to set email alerts
|

Psychological issues in acquired facial trauma

Abstract: The face is a vital component of one's personality and body image. There are a vast number of variables that influence recovery and rehabilitation from acquired facial trauma many of which are psychological in nature. The present paper presents the various psychological issues one comes across in facial trauma patients. These may range from body image issues to post-traumatic stress disorder symptoms accompanied by anxiety and depression. Issues related to facial and body image affecting social life and genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…However, Hull et al in a prospective study of 39 patients with maxillofacial trauma reported a decrease in both depression levels (baseline: 14%; 1-month follow-up: 4%) and anxiety levels (baseline: 15%; 1-month follow-up: 7%) 7. This variable response has been attributed to several factors such as patient's social support, preexisting psychological disorders, substance abuse, and postoperative pain 8. Even the cause of facial trauma may have a differential effect on the psychological consequence with injuries sustained as a result of assault associated with poor psychological outcomes 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Hull et al in a prospective study of 39 patients with maxillofacial trauma reported a decrease in both depression levels (baseline: 14%; 1-month follow-up: 4%) and anxiety levels (baseline: 15%; 1-month follow-up: 7%) 7. This variable response has been attributed to several factors such as patient's social support, preexisting psychological disorders, substance abuse, and postoperative pain 8. Even the cause of facial trauma may have a differential effect on the psychological consequence with injuries sustained as a result of assault associated with poor psychological outcomes 9.…”
Section: Discussionmentioning
confidence: 99%
“…7 This variable response has been attributed to several factors such as patient's social support, preexisting psychological disorders, substance abuse, and postoperative pain. 8 Even the cause of facial trauma may have a differential effect on the psychological consequence with injuries sustained as a result of assault associated with poor psychological outcomes. 9 An important factor in recovery from any trauma is family support.…”
Section: Discussionmentioning
confidence: 99%
“…The face also feels and it exudes identity. Severe facial disfigurement can contribute to social death (21,22), but facial transplant can potentially be a treatment as shown below: F1: “At present, the patient says she is not afraid of walking in the street or meeting people at a party, and she is very satisfied with the aesthetic and functional results.” VCA team reporting on outcome of female patient, 10 months postface transplant (26). F2: “Since the day of the operation, I have a face like everybody else.” Female patient, 1 year postface transplant (27).…”
Section: Resultsmentioning
confidence: 99%
“…Social death has been linked to increased mortality (biological death), including increased suicidal ideation and suicide attempts (11,12,19). Additional to homeless people, social death has been documented in many groups including the terminally ill (13), those with dementia (13,20), patients with coma (13), patients with facial disfigurement (21,22), victims of genocide (23), patients with severe burns (17,24), as well those with HIV/AIDS (25). This is the first analysis of social death in the field of VCA.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that patients who have sustained hand and upper limb traumas may suffer from acute and long-term psychological difficulties. A review by De Sousa et al 12 identified 209 articles that focused on psychological issues in hand trauma. Seventeen articles were further analyzed revealing commonly reported sequel which included posttraumatic stress disorder (PTSD), work avoidance, appearance and body image issues, sleep disturbance, pain, and psychosocial and marital functional difficulties.…”
Section: Introductionmentioning
confidence: 99%